Advancing two-phase wet gas flow measurement with Coriolis meters: optimal sensor orientation and a new model development - Salehi, Seyed Milad; Lao, Liyun; Simms, Nigel J.; Drahm, Wolfgang; Lin, Yaoying; Rieder, Alfred; Güttler, Andreas (Elsevier, 2025)
In this study, a novel wet gas model was developed based on the internal parameter of a Coriolis prototype to measure two-phase wet gas flow. Additionally, an optimal orientation of the Coriolis sensor was proposed to address challenges in the horizontal wet gas flow. Two Coriolis prototypes– one with a long-bent flow tubes (Type A), and another with short-bent flow tubes (Type B) – were employed to conduct tests in both vertical upward and horizontal pipelines. Different sensor axial angles (0, 40, 90, and 180°) were selected for testing in the horizontal section. Among different orientations (angles), it was found that the 40-degree angle outperforms the other installations in terms of the response proximity and over-reading of gas flow (OR). To understanding the impact of flow pattern on the response, a detailed analysis of different flow patterns in the wet gas was considered. A new correlation was developed between the damping factor of the Coriolis and both XLM and the total mass flow rate, leading to the proposal of a new wet gas model to predict gas and liquid flow rates with acceptable accuracy. In scenarios involving higher Froude numbers and annular flow patterns, which are more likely to occur, the Mean Absolute Percentage Error (MAPE) for the entire range of wetness (0 < XLM < 0.3) is 3.9 % for gas flow rate and 4.3 % for liquid flow rate with an uncertainty of 2.7 %.
Keywords: 4015 Maritime Engineering; 40 Engineering; Bioengineering; Mechanical Engineering & Transports; 4009 Electronics, sensors and digital hardware; 4012 Fluid mechanics and thermal engineering